Video education improves patients’ knowledge and satisfaction in treatment of solar lentigines with picosecond 755-nm alexandrite laser: A retrospective study - Liu, Jia-Wei; Tan, Yan; Chen, Tian; Qian, Yue-Tong; Zhang, Tao; Ma, Dong-Lai (Frontiers in Medicine, 2023)
Background: Picosecond lasers are widely used in dermatologic and cosmetic practice. In clinical practice, informed consent for laser treatments is critical to ensure patients' understanding of health information. Objectives: To evaluate whether video-based informed consent improves patient comprehension and satisfaction Methods: The study was performed from August 1 to November 30, 2022. Solar lentigines patients who fulfilled the inclusion criteria were included. Before October 1, 2022, traditional informed consent methods were performed. In the subsequent two months, a video-based informed consent was used as an adjunct to traditional consenting methods. Finally, patient comprehension of relevant knowledge about laser treatment and client satisfaction were assessed. Results: A total of 106 patients were included. The mean number of correct answers in the comprehension assessment in the video-based informed consent group was significantly higher than that in the traditional informed consent group (4.4±1.2 vs 3.4±1.1, P＜0.001). Compared to the traditional informed consent group, more correct answers in the video-based informed consent group were provided by older patients (3.9±1.2 vs 2.9±1.1, P=0.004) and patients with lower education levels (4.1±1.1 vs 3.0±1.2, P＜0.001). The mean satisfaction score in the video-based informed consent group was significantly higher than that in the traditional informed consent (27.8±5.7 vs 24.3±6.2, P=0.003). Conclusion: Video-based informed consent helps patients learn clinical literacy more effectively and improves patient satisfaction, especially in those with lower education levels and older ages.